Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 5 - Section 5.5 - Factoring Special Forms - Exercise Set: 16

Answer

$(x-y-6)(x+y-6)$

Work Step by Step

RECALL: A difference of two squares can be factored using the formula: $a^2-b^2=(a-b)(a+b)$ Factor the given difference of two squares using the formula above with $a=x-6$ and $b=y$ to obtain: $=[(x-6)-y][(x-6)+y] \\=(x-6-y)(x-6+y) \\=(x-y-6)(x+y-6)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.